PENGARUH IKLIM ORGANISASI, MOTIVASI TERHADAP KINERJA DENGAN MEDIASI KOMITMEN ORGANISASIONAL - Istadi, Rebo (Students Journal of Economic and Management, 2012)
This study aimed to infestigate the influence of organizational climate and work motivation to employee performance with the mediation organizational commitment the Secretariat of Batang Regency. In this study population was made the object of all employees at the Sekretariat of Batang Regency. In this study sampling using census methods are all members of the population being sampled. So the number of samples in this study were 160 respondents. The research proves to correctly describe the relationship of organizational climate, motivation and organizational commitment is 39,1% of the performance of the employee and the other at 60,9% defined for variables outside the model. The results of the regression analysis states that organizational climate and work motivation positive effect on organizational commitment. Organizational climate, motivation and organizational commitment positive effect to employee performance. The test results of mediation states that organizational commitment does not mediate the organizational climate and work motivation to employee performance. Keywords : Oerganizational climate, motivation, organizational commitment and employee performance